2000
DOI: 10.1191/026921500675826560
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping in spouses of persons with spinal cord injuries

Abstract: The identification of the potential at-risk group indicates that spouses of persons with SCI suffer levels of stress comparable to those of their injured partners. Rehabilitation plans should include this potential at-risk group to help them release the stress and to prevent them from developing clinically significant mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 17 publications
1
54
0
Order By: Relevance
“…Generally, it is the wife who carries the burden of care. Chan 13 In this study, it was found that the caregiver spends an average of 11.3 h per day caring for the person with SCI, which reflects an almost complete dedication, and is also responsible for housekeeping tasks and the care of other dependent family members. In Brazil, it is part of the culture to provide total support to relatives with disabilities or with special needs.…”
Section: Discussionmentioning
confidence: 80%
“…Generally, it is the wife who carries the burden of care. Chan 13 In this study, it was found that the caregiver spends an average of 11.3 h per day caring for the person with SCI, which reflects an almost complete dedication, and is also responsible for housekeeping tasks and the care of other dependent family members. In Brazil, it is part of the culture to provide total support to relatives with disabilities or with special needs.…”
Section: Discussionmentioning
confidence: 80%
“…Assistance of other family members' towards caregiving chores has been reported in minority ethnic groups and other cultures. 4,12,26,27 Although paid care support is a common feature in Western countries, 19,28 it is almost non-existent in a developing country like Fiji. Thus, the gap in the continuation of care is most likely filled by others present around these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2 The effects of SCI are catastrophic not only to the once active, independent person but also to the family and the society as a whole. 3 With advances in the medical and rehabilitation services, the life expectancy of persons with SCI has markedly increased, and in many cases it has approached that of the general population, [3][4][5] requiring varied levels of assistance over their lifespan. 5 With a change in the health-care system, early discharge towards community living settings has increased the responsibilities of informal family caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Several studies have shown negative effects of giving support on the quality of life of the caregivers of persons with SCI. 11,[14][15][16][17][18][19] Weitzenkamp et al studied stress and depression in 124 spouses of persons with SCI that had been injured more than 23 years ago. Spouses who were caregivers reported higher levels of stress, burnout, fatigue, resentment and depression compared to spouses who were not caregivers.…”
Section: Introductionmentioning
confidence: 99%